Removal of Wall-Adherent Inferior Vena Cava Thrombus with a Combined Approach Using Vacuum-Assisted Thrombectomy and a Rotational Thrombectomy Device - Julius Kaemmel; Roland Heck; Pia Lanmüller; Volkmar Falk; Christoph Starck (Case Reports in Vascular Medicine)
Introduction. Large thrombi in the inferior vena cava pose a high risk for a pulmonary embolism. Percutaneous extracorporeal circulation-based vacuum-assisted thrombus aspiration is a viable option for removal. Wall adherence of thrombotic material can compromise procedural success. Case Report. A 46-year-old female presented with a subtotal thrombotic occlusion of the inferior vena cava and the proximal right common iliac vein after weaning from extracorporeal life support. Due to severe wall adherence of the thrombotic material, the patient was treated with the combination of percutaneous extracorporeal circulation-based thrombus aspiration using the AngioVac system and a rotational thrombectomy device.